Odyssey Self Reflection - Skater / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif
Since playing skateboard has become my hobby, so I decided to produce my artworks about a girl who can play skateboard. In my artwork, the artworks have reflected myself where a girl wearing heels playing skateboard